THINK IT THROUGH: FOSTERING AESTHETIC EXPERIENCES TO RAISE INTEREST IN LITERATURE AT THE HIGH SCHOOL LEVEL - Lemieux, Amélie (Journal of the Canadian Association for Curriculum Studies, 2015)
French Quebec literature has always served as a cultural reference for the Quebec curriculum, and is still the means through which French language skills are most often taught in secondary 5 (grade 11) Quebec classrooms. In this paper, I suggest an interactive teaching of the Quebec play Incendies in three secondary 5 classrooms. Students’ meaning making responses, as elicited by qualitative data, provide an understanding of directions a teacher might take to increase interest in reading. These patterns of reactions further equip teachers with concrete tools to guide students in their reading. The purpose of this mixed methods study, in which quantitative data supported qualitative findings, was to see whether an intervention using personal maps (i.e., aesthetigrams) would increase interest in French Quebec literature. To this end, pre-tests, a map making intervention, and post-tests were given to 71 female high school participants in response to scene 37 of Incendies. The researcher pre-identified four main categories that guided students in their response process to literature. This process allowed students to reflect on their personal values and develop their agency in their learning. The following article informs researchers and practitioners alike of the effectiveness of aesthetigrams in literature pedagogy.